TRANSFORMASI GERAKAN TAJDID DI ERA DISRUPSI: ANALISIS FILOSOFIS DAN STRATEGIS MUHAMMADIYAH MENUJU ISLAM BERKEMAJUAN - Riska Putri Rusnadi; Sitti Aisyiah; Dahlan Lama Bawa (STKIP Subang, 2026)
This research is based on the importance of transforming the tajdid movement as a key determinant of the success of Islamic da'wah in the era of disruption, which often faces challenges in the relevance of strategies and adaptation of information technology. This research aims to conduct a comprehensive analysis of the historical roots, the vision of